Digital Sound Studies - Lingold, Mary Caton; Mueller, Darren; Trettien, Whitney (Duke University Press, 2018)
The digital turn has created new opportunities for scholars across disciplines to use sound in their scholarship. This volume's contributors provide a blueprint for making sound central to research, teaching, and dissemination. They show how digital sound studies has the potential to transform silent, text-centric cultures of communication in the humanities into rich, multisensory experiences that are more inclusive of diverse knowledges and abilities. Drawing on multiple disciplines-including rhetoric and composition, performance studies, anthropology, history, and information science-the contributors to Digital Sound Studies bring digital humanities and sound studies into productive conversation while probing the assumptions behind the use of digital tools and technologies in academic life. In so doing, they explore how sonic experience might transform our scholarly networks, writing processes, research methodologies, pedagogies, and knowledges of the archive.